2016
DOI: 10.1038/srep28693
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial phosphoenolpyruvate carboxykinase (PEPCK-M) and serine biosynthetic pathway genes are co-ordinately increased during anabolic agent-induced skeletal muscle growth

Abstract: We aimed to identify novel molecular mechanisms for muscle growth during administration of anabolic agents. Growing pigs (Duroc/(Landrace/Large-White)) were administered Ractopamine (a beta-adrenergic agonist; BA; 20 ppm in feed) or Reporcin (recombinant growth hormone; GH; 10 mg/48 hours injected) and compared to a control cohort (feed only; no injections) over a 27-day time course (1, 3, 7, 13 or 27-days). Longissimus Dorsi muscle gene expression was analyzed using Agilent porcine transcriptome microarrays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 61 publications
7
69
2
Order By: Relevance
“…Phosphorylation of effector molecules in the insulin-like growth factor (IGF)-stimulated protein synthesis pathway, mTOR and S6RP, was significantly enhanced after combined activin B and myostatin prodomain treatment. In addition, RNA-Seq showed that complete inhibition of Smad2/3 signaling in muscle resulted in markedly increased expression of growth factor (Igf2, increased 2.4-fold), amino acid transport (Slc7a5, fourfold; Lat2, 3.8-fold), and amino acid biosynthesis (Psat1, 3.7-fold) genes critical for protein synthesis (33)(34)(35). In terms of protein degradation, the expression of the E3 ubiquitin ligases Fbxo32 (MAFbx/atrogin1), Trim63 (MuRF1), and Fbxo30 (Musa1) (7,22), which classically drive this pathway in muscle, was not substantially reduced after 8 wk of myostatin/activin blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of effector molecules in the insulin-like growth factor (IGF)-stimulated protein synthesis pathway, mTOR and S6RP, was significantly enhanced after combined activin B and myostatin prodomain treatment. In addition, RNA-Seq showed that complete inhibition of Smad2/3 signaling in muscle resulted in markedly increased expression of growth factor (Igf2, increased 2.4-fold), amino acid transport (Slc7a5, fourfold; Lat2, 3.8-fold), and amino acid biosynthesis (Psat1, 3.7-fold) genes critical for protein synthesis (33)(34)(35). In terms of protein degradation, the expression of the E3 ubiquitin ligases Fbxo32 (MAFbx/atrogin1), Trim63 (MuRF1), and Fbxo30 (Musa1) (7,22), which classically drive this pathway in muscle, was not substantially reduced after 8 wk of myostatin/activin blockade.…”
Section: Discussionmentioning
confidence: 99%
“…For a full description of the study design, see 14 from which the samples used herein were generated. The project was approved by The University of Nottingham Ethical Review Committee and conducted in accordance with the UK Animals (Scientific Procedures) Act of 1986 (Project License PPL 40/3010).…”
Section: Methodsmentioning
confidence: 99%
“…These studies revealed impressive alterations in gene expression by BA, but the strength of the data set was limited by the use of only 2 time points. We recently 14 expanded on these studies, employing a pig microarray to analyse temporal changes to the pig skeletal muscle transcriptome in response to BA and growth hormone (GH) administration spanning ~4 weeks, using time points at 1, 3, 7, 13 and 27 days, which, to date, is the most comprehensive data set of its kind. In that study 14 , we identified coordinate increases in expression of mitochondrial phosphoenolpyruvate carboxykinase 2 (PEPCK-M) and 3-phosphoglycerate dehydrogenase (PHGDH) in response to BA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Brown et al suggested that increased expression of PHGDH genes enhanced the skeletal muscle growth in ractopamine treated pigs. 36 Furthermore, upregulation of PHGDH gene was correlated with higher muscle content in broilers. 37 Ankyrin Repeat Domain 2 (ANKRD2) prominently expressed in skeletal than cardiac muscle, which played an intriguing role in skeletal muscle plasticity.…”
Section: Discussionmentioning
confidence: 96%